If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = 19 + -4x Solving 7 + -3x = 19 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 7 + -3x + 4x = 19 + -4x + 4x Combine like terms: -3x + 4x = 1x 7 + 1x = 19 + -4x + 4x Combine like terms: -4x + 4x = 0 7 + 1x = 19 + 0 7 + 1x = 19 Add '-7' to each side of the equation. 7 + -7 + 1x = 19 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 19 + -7 1x = 19 + -7 Combine like terms: 19 + -7 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 2.6p+4=18p+12 | | 2.6+4=18+12 | | 3(2y+3)-4=-3 | | -x^4-14x^2+15=0 | | 5-2x=13-7x | | x^4-14x^2+15=0 | | -5x+3y=6 | | 13y^2-117y+104=0 | | 9x-42=4x-7 | | 1.8x+29=4x-4 | | 30x^2-18x-12=0 | | 0.625b-6=0.5b+12 | | 6y^2-22y-40= | | (7X+18)=67 | | 3x-4x=-13 | | 4x^2-8x+7=0 | | x+0.1x=-25.4 | | 0.75w-5=1-0.75w | | 3x^3+9=0 | | (4x^2-2x)+1= | | 5y-5=-26-2y | | x^3-12x^2+32x= | | -3x^2+75= | | j=38n-4 | | (3x^2+4x-1)(x)+(3x^2+4x-1)(4)= | | -10x+7=-23 | | 20x^3=5x | | 3(2*+1)-4*=1*+19 | | -3x(x-8)= | | 10c^2+29c+10= | | (2x-7)(7x+2)= | | 10-29c+10c^2= |